Response of phytoplankton photophysiology to varying environmental conditions in the Sub-Antarctic and Polar Frontal Zone. - Wee Cheah; Andrew McMinn; F Brian Griffiths; Karen J Westwood; Simon W Wright; Lesley A Clementson (PLoS ONE)
Climate-driven changes are expected to alter the hydrography of the Sub-Antarctic Zone (SAZ) and Polar Frontal Zone (PFZ) south of Australia, in which distinct regional environments are believed to be responsible for the differences in phytoplankton biomass in these regions. Here, we report how the dynamic influences of light, iron and temperature, which are responsible for the photophysiological differences between phytoplankton in the SAZ and PFZ, contribute to the biomass differences in these regions. High effective photochemical efficiency of photosystem II (F'(q)/F'(m)0.4), maximum photosynthesis rate (P(B)(max)), light-saturation intensity (E(k)), maximum rate of photosynthetic electron transport (1/[Symbol: see text]PSII), and low photoprotective pigment concentrations observed in the SAZ correspond to high chlorophyll a and iron concentrations. In contrast, phytoplankton in the PFZ exhibits low F'(q)/F'(M) (~ 0.2) and high concentrations of photoprotective pigments under low light environment. Strong negative relationships between iron, temperature, and photoprotective pigments demonstrate that cells were producing more photoprotective pigments under low temperature and iron conditions, and are responsible for the low biomass and low productivity measured in the PFZ. As warming and enhanced iron input is expected in this region, this could probably increase phytoplankton photosynthesis in this region. However, complex interactions between the biogeochemical processes (e.g. stratification caused by warming could prevent mixing of nutrients), which control phytoplankton biomass and productivity, remain uncertain.